2016
DOI: 10.1136/bmjopen-2015-010935
|View full text |Cite
|
Sign up to set email alerts
|

Associations of neonatal high birth weight with maternal pre-pregnancy body mass index and gestational weight gain: a case–control study in women from Chongqing, China

Abstract: ObjectivesTo examine the associations of maternal pre-pregnancy body mass index (BMI) and gestational weight gain (GWG) with neonatal high birth weight (HBW) in a sample of Chinese women living in southwest China.MethodsA hospital-based case–control study was conducted in Chongqing, China. A total of 221 mothers who delivered HBW babies (>4.0 kg) were recruited as cases and 221 age-matched (2-year interval) mothers with normal birth weight babies (2.5–4.0 kg) were identified as controls. ORs were estimated usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 35 publications
0
14
0
3
Order By: Relevance
“…Multiple studies from middle and high income countries have found that women with inadequate GWG were at a higher risk of giving birth to LBW and preterm infants [ 5 , 12 16 ]. Women in LICs generally have lower weight and GWG than those in high income countries [ 17 ]. More than 95% of LBW infants are born in LICs—sub-Saharan Africa alone has a 15% incidence of LBW [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies from middle and high income countries have found that women with inadequate GWG were at a higher risk of giving birth to LBW and preterm infants [ 5 , 12 16 ]. Women in LICs generally have lower weight and GWG than those in high income countries [ 17 ]. More than 95% of LBW infants are born in LICs—sub-Saharan Africa alone has a 15% incidence of LBW [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prenatal and in utero growth is dependent upon maternal nutritional status, and growing evidence has demonstrated that the latter is often correlated with GWG and pre-pregnancy BMI [29]. According to Moroccan Ministry of Health recommendations, GWG should never be less than 7 kg in obese or overweight women [30].…”
Section: Macrosomia Risk Factorsmentioning
confidence: 99%
“…Generally, data show an average gestational weight gain of 19.7 ± 5.1 kg. [16] Here, the patient's weight was 46 kg before pregnancy, and her weight was 62.5 kg before delivery, indicating a 16.5-kg increase. Abdominal weight gain could have increased the stress concentration and overtaxed the instruments, resulting in kyphosis progression and, ultimately, rod breakage.…”
Section: Discussionmentioning
confidence: 97%